ROLE OF ACT EAST POLICY IN THE DEVELOPMENT OF NORTH EAST INDIA: EXPECTATION VS. REALITY - Devasish Hazarika (International Journal of Modern Agriculture, 2021)
Act east policy has been undertaken to develop the North East region. There is a huge gap between expectation and reality. This paper is descriptive and analytical one. In this paper it is attempted to find out the flaws of the policy.The purpose of the Look east policy was to maintain a good relationship with eastern countries namely Japan, Australia, ASEAN countries. India exported U.S. 10.41 billion in 2005-06 to ASEAN which increased to U.S. 25.20 billion in 2015-16 and imports over the same period quadrupled from U.S. 10.8 billion in 2005-06 to U.S. 39.84 billion. This reflects a compound annual growth rate of about 9.2% in exports to ASEAN region and close to 14% p.a growth in imports during 2005-06 to 2015-16. In terms of market share, the share of import in Indiaâ€™s total imports from ASEAN went up from 7.3% to 10.5% during 2005-06 to 2015-16. Over the same period the share of export to ASEAN in Indiaâ€™s total export fell from 10.1% to 9.6%.A good move was made by the Government of India by signing the Act East Policy because the North Eastern Part of the country couldn’t progress at par with the rest of India. Therefore, to remove several bottlenecks in terms of connectivity, market access and investment requirements , the Act East Policy was very strategic.